Estrategias de mercadeo y comercialización de la papa (solanum tuberosum o s. Andigenum) para los mercados de la ciudad de Loja - Torres Troya, Dany Leonel (2015)
This research developed in the canton Loja province of Loja, aimed at: 1) Analyze the current and future supply and demand of potato production. 2) Study the technical-economic and social implications of the commercialization process of the potato. 3) Identify market strategies that enable producers to achieve sustainable production. 4) To disseminate research results to stakeholders. The methodology included the collection of secondary information in libraries and public institutions; and primary through surveys three strata of the population such as producers, traders and consumers of potatoes; he joined it, the dissemination of results and approach, in a participatory manner, the marketing strategy and marketing. The variables studied were supply, demand, competition and marketing systems. The results established two important sectors demanding: Direct which are final and indirect consumers, restaurants, and soda fountains. Similarly, they threw two systems marketing direct and indirect consumer end with the presence of wholesalers, retailers, independent brokers, intermediaries industrial, warehouse and transportation. Marketing strategies that make concerning the association for both production and marketing were raised; functional market mechanisms; postharvest system; alternative marketing channels; and permanent production.